An ergonomic evaluation of tasks of healthcare unit personnel in different shifts in General Hospitals in West Bengal - Subhashis Sahu; Smaranika Goswami; Prasun Haldar; Moumita Sett (Occupational Health and Safety Society of Nepal, 2012)
The job challenges faced by healthcare unit personnel are psychological, temporal and physically demanding. Studies on psychological stress on nurses are available but unfortunately studies on physiological load or temporal anal ysis of tasks of nurses or attendants in general hospitals in India have not been reported so far. The study aims at evaluating the perception of workload in different shifts among healthcare unit personnel and to develop better ergonomic management protocols. The study population comprised 150 staff nurses and 175 attendants working in three government hospitals in West Bengal, India. The amount of time spent by nurses and attendants performing different tasks were recorded throughout the shifts using an activity analysis chart along with perceived exertion rating and heart rate throughout the shifts. About 26.8% of the total working time throughout the day was spent in "direct care". In case of general duty attendants 24.4% of the duty time was spent in indirect care. Time spent in different tasks differed by shifts. More leisure time occured in the night shift compared to the morning and afternoon shifts but duration of shift was longer (11 to 12 hours). Perceived exertion rating of healthcare unit personnel in night shift was more compared to other shifts but physiological response did not reflect that. There were temporal variations of job demand in healthcare units. So, ergonomic orientation of layouts of departments, arrangement of activities, ergonomic way of keeping the records and use of proper communication system, were recommended reducing the stress of healthcare unit personnel.